Typological Features Of Dictionaries - Jurabaev Bahodir Rakhimovich (Genius Journals, 2022)
The article is devoted to the study and analysis of typologies and classifications of dictionaries. The problem of typologies of dictionaries has been discussed for more than a dozen years. It can be argued that this area is becoming more and more interesting. A considerable amount of time is devoted to the classification of dictionaries. The typology of dictionaries is based on the concept of an ideal dictionary
Keywords: Dictionary; Typology; Trend; Classification